2017
DOI: 10.3389/fimmu.2016.00667
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Restriction Attenuates Terminal Differentiation of Immune Cells

Abstract: Immune senescence is a natural consequence of aging and may contribute to frailty and loss of homeostasis in later life. Calorie restriction increases healthy life-span in C57BL/6J (but not DBA/2J) mice, but whether this is related to preservation of immune function, and how it interacts with aging, is unclear. We compared phenotypic and functional characteristics of natural killer (NK) cells and T cells, across the lifespan, of calorie-restricted (CR) and control C57BL/6 and DBA/2 mice. Calorie restriction pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 69 publications
1
21
1
Order By: Relevance
“…Previous work has shown that immune responses can be strongly affected by the amount and/or balance of nutrients in the diet e.g. (Fernandes et al, 1976; Ingram et al, 1995; Kristan, 2008; Le Couteur et al, 2015; Lee et al, 2006; Nayak et al, 2009; Povey et al, 2009; Ritz and Gardner, 2006; Wallace et al, 1999; White et al, 2017). However, most of these studies covered only a relatively small region of nutrient space (Fernandes et al, 1976; Ingram et al, 1995; Lee et al, 2006; Nayak et al, 2009; Povey et al, 2009; Ritz and Gardner, 2006; White et al, 2017) and/or only tested innate responses (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that immune responses can be strongly affected by the amount and/or balance of nutrients in the diet e.g. (Fernandes et al, 1976; Ingram et al, 1995; Kristan, 2008; Le Couteur et al, 2015; Lee et al, 2006; Nayak et al, 2009; Povey et al, 2009; Ritz and Gardner, 2006; Wallace et al, 1999; White et al, 2017). However, most of these studies covered only a relatively small region of nutrient space (Fernandes et al, 1976; Ingram et al, 1995; Lee et al, 2006; Nayak et al, 2009; Povey et al, 2009; Ritz and Gardner, 2006; White et al, 2017) and/or only tested innate responses (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…(Fernandes et al, 1976; Ingram et al, 1995; Kristan, 2008; Le Couteur et al, 2015; Lee et al, 2006; Nayak et al, 2009; Povey et al, 2009; Ritz and Gardner, 2006; Wallace et al, 1999; White et al, 2017). However, most of these studies covered only a relatively small region of nutrient space (Fernandes et al, 1976; Ingram et al, 1995; Lee et al, 2006; Nayak et al, 2009; Povey et al, 2009; Ritz and Gardner, 2006; White et al, 2017) and/or only tested innate responses (e.g. (Fernandes et al, 1976; Ingram et al, 1995; Le Couteur et al, 2015; Lee et al, 2006; Nayak et al, 2009; Povey et al, 2009; White et al, 2017) or the response to an artificial pathogen or immune stimulant (Cotter et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, metabolic status could affect the functions of immune cells. Caloric restriction has exhibited systemic antiinflammatory effects, along with attenuated terminal differentiation of immune cells (111). Given the energy sensing properties of AMPK, the AMPK-ULK1-TBK1 axis may also function in immune cells to mediate anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…The thymus is one of the major lymphoid organs in the immune system, and several studies have reported that calorie restriction (CR) potentiates thymic function [ 2 , 28 , 60 ]. RNA were isolated from thymus tissue of ad libitum, chronic calorie restriction, and intermittent calorie restriction diet MMTV-TGF- α mice from 10 weeks of age to 17 weeks of age or 18 weeks of age.…”
Section: Discussionmentioning
confidence: 99%